REPEATABILITY AND LONGITUDINAL ASSESSMENT OF FOVEAL CONE STRUCTURE IN CNGB3-ASSOCIATED ACHROMATOPSIA. Issue 10 (October 2017) - Langlo, Christopher S.; Erker, Laura R.; Parker, Maria; Patterson, Emily J.; Higgins, Brian P.; Summerfelt, Phyllis; Razeen, Moataz M.; Collison, Frederick T.; Fishman, Gerald A.; Kay, Christine N.; Zhang, Jing; Weleber, Richard G.; et al.
Abstract : Purpose: Congenital achromatopsia is an autosomal recessive disease causing substantial reduction or complete absence of cone function. Although believed to be a relatively stationary disorder, questions remain regarding the stability of cone structure over time. In this study, the authors sought to assess the repeatability of and examine longitudinal changes in measurements of central cone structure in patients with achromatopsia. Methods: Forty-one subjects with CNGB3 -associated achromatopsia were imaged over a period of between 6 and 26 months using optical coherence tomography and adaptive optics scanning light ophthalmoscopy. Outer nuclear layer (ONL) thickness, ellipsoid zone (EZ) disruption, and peak foveal cone density were assessed. Results: ONL thickness increased slightly compared with baseline (0.184 μ m/month, P = 0.02). The EZ grade remained unchanged for 34/41 subjects. Peak foveal cone density did not significantly change over time (mean change 1% per 6 months, P = 0.126). Conclusion: Foveal cone structure showed little or no change in this group of subjects with CNGB3- associated achromatopsia. Over the time scales investigated (6–26 months), achromatopsia seems to be a structurally stable condition, although longer-term follow-up is needed. These data will be useful in assessing foveal cone structure after therapeutic intervention. Abstract : High-resolution in vivo imaging has provided evidence of residual cone structure in congenital achromatopsia, although the progressive nature of the disease remains unclear. In this study, the authors use optical coherence tomography and adaptive optics scanning light ophthalmoscopy to investigate longitudinal changes in cone structure in achromatopsia.